Mgat5 Deficiency in T Cells and Experimental Autoimmune Encephalomyelitis - Grigorian, Ani (International Scholarly Research Network, 2011)
Multiple sclerosis (MS) is an inflammatory demyelinating and neurodegenerative disease initiated by autoreactive T cells. Mgat5, a gene in the Asn (N-) linked protein glycosylation pathway, associates with MS severity and negatively regulates experimental autoimmune encephalomyelitis (EAE) and spontaneous inflammatory demyelination in mice. N-glycan branching by Mgat5 regulates interaction of surface glycoproteins with galectins, forming a molecular lattice that differentially controls the concentration of surface glycoproteins. T-cell receptor signaling, T-cell proliferation, T(H)1 differentiation, and CTLA-4 endocytosis are inhibited by Mgat5 branching. Non-T cells also contribute to MS pathogenesis and express abundant Mgat5 branched N-glycans. Here we explore whether Mgat5 deficiency in myelin-reactive T cells is sufficient to promote demyelinating disease. Adoptive transfer of myelin-reactive Mgat5(−/−) T cells into Mgat5(+/+) versus Mgat5(−/−) recipients revealed more severe EAE in the latter, suggesting that Mgat5 branching deficiency in recipient naive T cells and/or non-T cells contribute to disease pathogenesis.